1997
DOI: 10.1149/1.1837495
|View full text |Cite
|
Sign up to set email alerts
|

Li‐Ion Battery Electrolyte Formulated for Low‐Temperature Applications

Abstract: Low‐temperature (<0°C) applications of Li‐ion batteries have prompted the search for improved, high‐conductivity electrolytes. Because the performance of the carbonaceous anode is highly sensitive to changes in electrolyte composition, we focused our efforts on this electrode. Electrolytes containing LiAsF6,LiPF6,normalLiNfalse(SO2CF3)2 [lithium bis(trifluoromethanesulfonyl)imide], or LiIm, and normalLiCfalse(SO2CF3)3 [lithium tris(trifluoromethanesulfonyl)methide], or LiMe, in methyl formate (MF)‐ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 6 publications
1
60
0
Order By: Relevance
“…At −30 • C, the electrode had little or no capacity at the rates used. The drop-off in capacity as a function of temperature and rate is in good agreement with previously reported results [7,33].…”
Section: Electrochemical Characterizationsupporting
confidence: 92%
“…At −30 • C, the electrode had little or no capacity at the rates used. The drop-off in capacity as a function of temperature and rate is in good agreement with previously reported results [7,33].…”
Section: Electrochemical Characterizationsupporting
confidence: 92%
“…Therefore, the authors speculated that the SEI formed in the presence of low molecular weight esters appeared to be resistive and inadequately protective, whereas, in the presence of esters of higher molecular weight, the SEI could be formed with more desirable attributes. Combining the observations of Ein-Eli et al, 102 Smart et al, 461,462 and Herreyre et al, 406 it could be tentatively concluded that longer alkyl chains in the carboxylic acid section of the esters play a critical role in determining the cathodic stability of this component on a graphite anode. The tests in AA-size full lithium ion cells were only reported for EA-and MA-based quaternary electrolytes, and Figure 59 shows the discharging profiles of these cells at -40°C.…”
Section: Solvent Approachmentioning
confidence: 66%
“…As the performances of LIC cells at low temperature are mainly limited by carbon anode [25], further work on anode electrode remains to be undertaken, such as: (i) forming more effective conductive network to enhance the electric conductivity by the addition of carbon nanotube and/or graphene [35]; (ii) forming porous anode electrode to increase electrolyte uptake and reduce ionic transport path, facilitating lithium-ion diffusion from/to lithium intercalation sites by the adoption of porous graphite or nongraphite carbon [7,36,37]; (iii) using special electrolytes which are suitable for low-temperature operation to improve the lithium-ion concentration and mobility [24]; (iv) increasing lithium capacity of anode by raising the mass of active materials in anode or reducing the pre-lithiation degree. Nevertheless, the lithium plating and the growth of lithium dendrites in anode should be managed to be avoided during high-rate charging process at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…It increases the risk of the lithium dendrite formation and growth on anode surface at high-rate charging processes, which can lead to the internal short-circuit failure of cells. The low cut-off potential of anode at low temperature is due to the decrease of the concentration of salt (LiPF 6 ) and the lithium-ion mobility [24] and the increase of the activation energy for lithium-ion diffusion and intercalation in carbon anode [25]. For LIC cells, the AC cathode is involved in the anion double-layer formation without obvious bulk redox.…”
Section: Methodsmentioning
confidence: 99%